Observations of internal tidal dynamics Southwest of Malta in the central Mediterranean Sea. (1st February 2023) - Poulain, Pierre-Marie; Oddo, Paolo; Pennucci, Giuliana; Lewis, Craig; Sliwka, Jan; Duda, Timothy Frederick; Drago, Aldo
Abstract: Internal tidal dynamics are investigated southeast of Malta in the central Mediterranean using temperature, salinity, and current data from moorings on the shelf, slope, and deep sea. The greatest variability below the mixed surface layer and the sharp thermocline (below 60 m) is at the diurnal K1 tidal frequency, with the signal being significantly enhanced from the deep sea to the shelf and being fortnightly modulated. Harmonic analysis shows that the diurnal vertical displacements at the shelf break can reach an amplitude of 15–25 m at 160 m depth. The corresponding vertical velocities are ∼0.1–0.2 cm s −1 . Horizontal currents are maximum (10–15 cm s −1 ) at about the same depth. They rotate clockwise and counterclockwise above and below ∼160 m, respectively. The internal K1 tidal signal is interpreted as a northwestward propagating shelf wave with a phase velocity close to 1 m s −1 and a wavelength of the order of 100 km. Horizontal and vertical currents at semi-diurnal (M2) frequency are much smaller (less than 2–3 cm s −1 and ∼0.02 cm s −1, respectively). Highlights: The diurnal tide is dominant on the continental slope southeast of Malta. The tidal diurnal tidal signal is maximum near 160 m depth. Observations are interpreted as an internal wave propagating northwestward along the shelf.